A GENERAL VIEW OF THE HISTORICAL DEVELOPMENT OF PHYSICAL CULTURE AND PHYSICAL EDUCATION - Dragan Martinović; Dragan Branković; Vladimir Živanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Physical education has emerged as a business development and developed the awareness that this is one of the necessary conditions of general human, biological, psychological and sociological progress. Physical education as an activity has remained subordinate to historical conditions and circumstances. It thrived for many years as part of the overall development of individual and social conscious¬ness. Throughout the centuries, generations of people engaged in physical activities mo¬re or less freely, or involuntarily, with pleasure, and without him, but always with a purpose. Outlook on life, way of life and human needs have been changing with the development of human society. Patterns of development of a society, its changes in general also apply to the development of physical education. Need for physical education and the need for changes in physical education is one of its main characteristics. History has changed conceptual and ideological basis of physical education.